Penentuan Kadar Logam Tembaga pada Perairan dan Sedimen di Limbah Pertambangan Tradisional Desa Perabu Kabupaten Lombok Tengah - Firmansyah, Dodiy; Sustiyani, Elly (Lembaga Penelitian dan Pendidikan Mandala, 2021)
. Prabu’s people in central Lombok regency make traditional mining for their livelihood. Coppers are one of the wastes from traditional mining, which is dumped into rivers can pollute the waters used by humans a source of clean water. Heavy metals in biota consumed by humans and transmit various diseases, This research to determination copper compound in waters and sediments. The are two puposes of this reseach: (1) to determine coppers in waters and sediments, and (2) to determine copper compound. There are three steps of this reseach: (1) conducting sampling, (2) pretreatment of sediment samples, (3) determining heavy metal levels with the fraction 1 stepwise extraction method (ELFE), and (4) analyzing copper compound . The result showed that copper compound increasing in locations B and C, contain 0.065 mg / L and 0.051 mg / L in water and contain 89 mg/kg, 85 mg/kg in sediment